2012
DOI: 10.1111/j.1476-5381.2012.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

D‐carnosine octylester attenuates atherosclerosis and renal disease in ApoE null mice fed a Western diet through reduction of carbonyl stress and inflammation

Abstract: BACKGROUND AND PURPOSE Lipoxidation‐derived reactive carbonyl species (RCS) such as 4‐hydroxy‐2‐nonenal (HNE) react with proteins to form advanced lipoxidation end products (ALEs), which have been implicated in both atherosclerosis and renal disease. L‐carnosine acts as an endogenous HNE scavenger, but it is rapidly inactivated by carnosinase. This study aimed at assessing the effect of the carnosinase‐resistant, D‐carnosine, on HNE‐induced cellular injury and of its bioavailable prodrug D‐carnosine octylester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 42 publications
(58 reference statements)
8
70
0
Order By: Relevance
“…Several studies in rodents have recently reported protective effects of carnosine administration on dyslipidemia [lipid profile in plasma (3,25), cholesterol levels in heart and liver (21,25), atherosclerosis (23)] and blood pressure (3). In contrast to rodents, humans have the enzyme plasma carnosinase, and as we confirm in this study, its activity is highly variable between individuals.…”
Section: Low Plasma Carnosinase Content/activity Associated With Lipisupporting
confidence: 64%
See 1 more Smart Citation
“…Several studies in rodents have recently reported protective effects of carnosine administration on dyslipidemia [lipid profile in plasma (3,25), cholesterol levels in heart and liver (21,25), atherosclerosis (23)] and blood pressure (3). In contrast to rodents, humans have the enzyme plasma carnosinase, and as we confirm in this study, its activity is highly variable between individuals.…”
Section: Low Plasma Carnosinase Content/activity Associated With Lipisupporting
confidence: 64%
“…Finally, carnosine supplementation in streptozotocin-induced diabetic and dyslipidemic Balb/cA mice reduces triglyceride and cholesterol levels in heart and liver (21). The latter findings have been confirmed and extended in several other animal models of metabolic diseases (3,23,25). Whether the protective effects of carnosine ingestion in rodents can be translated to humans is not known, because rodents, unlike humans, have no carnosinase in their plasma (18).…”
supporting
confidence: 52%
“…Serum levels of isoprostane 8-epiprostaglandin (PG) F 2α were assessed using an ELISA kit (Cayman, Ann Arbor, MI, USA) and those of AGEs were measured by a competitive ELISA technique [17,19,20]. Serum and urine creatinine levels were measured by HPLC and proteinuria and albuminuria were assessed using the Bradford dye-binding protein assay kit (Pierce, Rockford, IL, USA) and the Mouse Albumin ELISA kit (Bethyl, Montgomery, TX, USA), respectively, and results were normalised to urine creatinine concentration [17,20].…”
Section: Methodsmentioning
confidence: 99%
“…Morphology/morphometry For the assessment of atherosclerotic lesions [17,19], the extent of lipid accumulation was evaluated in en face preparations after staining with Oil Red O. Lesion area was quantified at the aortic sinus and BCA level after staining with Oil Red O and the Weigert-van Gieson method for elastic and collagen fibres [21], respectively. Five cryosections of aortic sinus (10 μm thick, every other section) and four sections (5 μm thick) at 200, 400, 600 and 800 μm from the branching point of the BCA were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation